OP37 Family and school influences on two aspects of seven year-olds' social and emotional well-being: cross-sectional analysis using the Growing Up in Scotland study. (2nd September 2014) - Parkes, A; Sweeting, H; Wight, D
Abstract : Background: Social and emotional well-being covers several aspects of social and psychological functioning, but children's subjective wellbeing has not been as extensively researched as mental health problems and little is known about factors shaping subjective well-being in children younger than 10 years. This study of seven year-olds explored family and school influences on mother-reported child behavioural and emotional problems, and children's subjective well-being. Methods: Interview data were collected in 2012/13 from mothers and seven year-old children in 3279 families within the first birth cohort of the Growing Up in Scotland study. Mothers reported on the child's behavioural and emotional problems using the Strengths and Difficulties Questionnaire (SDQ), and children completed a 5-item version of the Huebner Student Life Satisfaction scale. Two multivariable models, one of mother-reported "high difficulties" (standard SDQ cut-off), and the other of low child-reported life satisfaction (lowest quartile), explored the role of child, maternal and household characteristics, parenting, school experiences, friendships, leisure activities, and materialistic attitudes. Some aspects of parenting and school were reported by mother and child, enabling comparison of effects according to information source. Results: 11% were identified as having "high difficulties"; 4% had "high difficulties" and reported low life satisfaction. Mother-reported measures associated with low life satisfaction included a family death/illness/accident (Odds Ratio 1.33, 95% Confidence Interval 1.10–1.61), high parent-child conflict (OR 1.50, 95% CI 1.16–1.96), less positive parenting (OR 1.56, 95% CI 1.13–2.13) and the child disliking school (OR 1.33, 95% CI 1.07–1.65). Conflict and school dislike were associated more strongly with "high difficulties" (ORs respectively 22.7, 95% CI 9.77–52.74 and 2.18, 95% CI 1.62–2.95), while a death/illness/accident and less positive parenting did not clearly differentiate "high difficulties". Child-reported measures associated with low life satisfaction included less positive parenting (OR 2.87, 95% CI 2.27–3.70), disliking school (OR 2.57, 95% CI 2.00–3.33), and poorer friendships (OR 2.08, 95% CI 1.60–2.69). Only poorer friendships were also associated with high difficulties (OR 2.26, 95% CI 1.46–3.52). Poor child and maternal health, low maternal education, and family mental health/substance use problems were associated with "high difficulties" but not low life satisfaction. Conclusion: Although the cross-sectional nature of this study limits interpretation, it provides rare data on seven year-old children. Findings extend existing literature on the importance of family processes and school experiences for children's life satisfaction and mental health, and suggest possible targets for intervention.